Evaluation of Students' Use of Visual Learning Representations in Science Classes: A Case Study from Turkey - Tufan Inaltekin; Volkan Goksu (Journal of Education in Science, Environment and Health)
TThe aim of this study was to analyse the kinds and frequency of visual learning representations within 8th grade students’ notebooks for science classes. As part of the research, 93 science notebooks which belonged to students from 13 secondary schools in Kars Province (the east of Turkey) were collected at the end of the academic year in 2018. Document analysis, a qualitative research strategy, has been adopted and content analysis technique was used to analyse the collected documents. The results showed that the visual learning representations recorded on students’ notebooks were notably different from one unit to another and from one school to another. Moreover, it has been observed that students did not make frequent use of visual representations whilst learning the content.  Additionally, the visual learning representations in students’ notebooks mostly consisted of the representations used by teachers during classes. These findings suggest that science teachers might have not been successful enough in guiding students to incorporate different visual representations into their learning processes for a better understanding of science subjects.